(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
It has become anecessity than anything else. Many networks are now emerging in India. Forparticipation and also the effective utilisation of network resources, it isnecessary for the participating members to automate their libraries. Althoughrequired hardware for library automation is now available at a reasonable cost;software packages are however not easily available. Before introducingautomation, a comprehensive evaluation of the library requirements, softwarefeatures needed, and capabilities of the hardware for implementing the softwarehas to be made.